Genetic modification of dividing cells using episomally maintained S/MAR DNA vectors - Suet-Ping Wong; Richard Paul Harbottle (Elsevier, 2013)
The development of episomally maintained DNA vectors to genetically modify dividing cells efficiently and stably, without the risk of integration-mediated genotoxicity, should prove to be a valuable tool in genetic research. In this study, we demonstrate the utility of Scaffold/Matrix Attachment Region (S/MAR) DNA vectors to model the restoration of a functional wild-type copy of the gene folliculin (FLCN) implicated in the renal cancer Birt-Hogg-Dubé (BHD). Inactivation of FLCN has been shown to be involved in the development of sporadic renal neoplasia in BHD. S/MAR-modified BHD tumor cells (named UOK257-FS) show restored stable FLCN expression and have normalized downstream TGFβ signals. We demonstrate that UOK257-FS cells show a reduced growth rate in vitro and suppression of xenograft tumor development in vivo, compared with the original FLCN-null UOK257 cell line. In addition, we demonstrate that mTOR signaling in serum-starved FLCN-restored cells is differentially regulated compared with the FLCN-deficient cell. The novel UOK257-FS cell line will be useful for studying the signaling pathways affected in BHD pathogenesis. Significantly, this study demonstrates the suitability of S/MAR vectors to successfully model the functional expression of a therapeutic gene in a cancer cell line and will aid the identification of novel cancer markers for diagnosis and therapy.